2021
DOI: 10.1097/md.0000000000025948
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupoint catgut embedding in treating postoperative pain of mixed hemorrhoids

Abstract: Background: Pain is a common complication after mixed hemorrhoids, which seriously affects the recovery of patients and prolongs the length of hospital stay. Acupoint catgut embedding has advantages in improving a variety of acute and chronic pain diseases, but there is still a lack of rigorous randomized controlled studies to verify its efficacy and safety in the treatment of postoperative pain of mixed hemorrhoids. Therefore, the purpose of this randomized controlled trial is to evaluate the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…A total of 5121 cases were included in 47 [ 7 , 9 – 54 ] studies. A total of 47 RCTs were included in this study, of which 17 evaluated auricular plaster versus common treatment [ 10 – 14 , 16 , 18 , 20 , 21 , 23 , 24 , 28 , 29 , 50 – 52 , 54 ], 8 evaluated auricular plaster versus painkillers [ 15 , 17 , 22 , 25 – 27 , 30 , 31 ], 5 evaluated acupoint catgut embedding versus common treatment [ 7 , 34 , 35 , 37 , 53 ], 7 evaluated acupoint catgut embedding versus painkillers [ 9 , 36 , 38 , 39 , 43 – 45 ], 6 evaluated acupoint application point versus common treatment [ 40 – 42 , 47 – 49 ], 1 evaluated acupoint application point versus painkillers [ 33 ], 1 evaluated auricular plaster and acupoint application point versus painkillers [ 32 ], and 2 evaluated auricular plaster and acupoint application point versus common treatment [ 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 5121 cases were included in 47 [ 7 , 9 – 54 ] studies. A total of 47 RCTs were included in this study, of which 17 evaluated auricular plaster versus common treatment [ 10 – 14 , 16 , 18 , 20 , 21 , 23 , 24 , 28 , 29 , 50 – 52 , 54 ], 8 evaluated auricular plaster versus painkillers [ 15 , 17 , 22 , 25 – 27 , 30 , 31 ], 5 evaluated acupoint catgut embedding versus common treatment [ 7 , 34 , 35 , 37 , 53 ], 7 evaluated acupoint catgut embedding versus painkillers [ 9 , 36 , 38 , 39 , 43 – 45 ], 6 evaluated acupoint application point versus common treatment [ 40 – 42 , 47 – 49 ], 1 evaluated acupoint application point versus painkillers [ 33 ], 1 evaluated auricular plaster and acupoint application point versus painkillers [ 32 ], and 2 evaluated auricular plaster and acupoint application point versus common treatment [ 19 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…47 literature were all two-arm studies. 34 studies [ 7 , 9 – 15 , 17 – 19 , 21 – 23 , 28 – 31 , 33 – 46 , 48 , 49 ] reported pain scores, 14 studies [ 9 , 13 , 16 , 17 , 19 , 20 , 22 , 24 – 27 , 39 , 42 , 47 ] reported the total efficiency, 9 studies [ 22 , 26 , 32 , 42 , 50 – 54 ] reported postoperative pain degree, and in terms of study design, 11 studies [ 11 , 14 , 17 , 28 , 29 , 32 , 33 , 36 , 43 , 45 , 46 ] reported adverse effects and detail management measures, 14 studies [ 11 , 15 , 17 , 19 , 34 – 36 , 40 , 42 , 43 , 46 , 47 , 52 , 54 ] used random number tables, and 20 studies [ 9 , 12 , 18 , 20 – 22 , 26 , 27 , 29 , 31 – 33 , 37 – 39 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations